Relationship Between Sociodemographic Differences and Knowledge, Attitude, and Anxiety Levels During the Coronavirus Disease 2019 Pandemic: A Cross-Sectional Study on Healthcare Workers in Turkey and South Africa - Güngördü, Nejdiye; Kara, Beril; Mosam, Atiya; Kurtul, Seher; Özşahin, Yasemin; Erkan, Arzu; Yılmaz AK, Hülya; Erdoğan, Mehmet Sarper (Cerrahpaşa Medical Journal, 2023)
Objective: The aim of this study is to evaluate the knowledge, attitude, and anxiety levels of healthcare workers in Turkey and South Africa and to determine the possible factors associated with anxiety. Methods: A cross-sectional study with 864 healthcare workers in Turkey and South Africa was conducted during May 1-October 30, 2020. The questionnaire included sociodemographic, individual, work-related, and about coronavirus disease 2019 questions. Anxiety was measured with the Beck Anxiety Inventory. Results: A total of 864 people answered the questionnaire, 527 from South Africa and 337 from Turkey. Healthcare workers in both countries have mild anxiety levels, and the median value of the Beck Anxiety Scale score was significantly higher in the participants from South Africa (10) than the participants in Turkey (8) (P = .004). Compared to Turkey, the risk of moderate/severe anxiety was 1.56 times higher in South Africa. Female gender, duties out of work definition, difficulties of chronic illness management, difficulties in accessing the treatment of mental health problem, living with a person who is older than 65 or has a comorbidity, and personal protective equipment support were found to be associated with moderate/severe anxiety (P < .05). Conclusion: In order to reduce the mental health impact on healthcare workers, pandemic readiness plans must take into account working hours and workload, adequate personal protective equipment supply, and measures to provide psychological support to healthcare workers, especially those with pre-existing mental health illnesses. Cite this article as: Güngördü N, Kara B, Mosam A, et al. The relationship between sociodemographic differences and knowledge, attitude and anxiety levels during the coronavirus disease 2019 pandemic: A cross-sectional study on healthcare workers in Turkey and South Africa. Cerrahpasa Med J. 2023;47(2):215-221.